Audio Steganography for Secure Data Transmission - Kundu, N; Kaur, A (International Journal of Computer Sciences and Engineering, 2025)
As the internet growing day by day secure transmission of information is crucial. Steganography and cryptography both techniques provide data confidentiality, integrity and help us to protect data from day by day attacks. Internet communication has become an essential part of infrastructure now a days and also lots of applications are internet based. So the communication made must be secret to avoid attacks. Steganography is a process of hiding the information of secret messages or one can say that it is an art of sending the hidden data or message over a public network. In the proposed approach message is first encrypted through using The Vigenere Square Encryption Algorithm. After those characters of information or data is embedded into deeper layers through modified LSB method. After that further audio transposition encryption technique is used for audio and accuracy for transposition method is measured in terms of MSE.